Outcomes of nonsuspicious contralateral nodules with active surveillance after lobectomy in patients with papillary thyroid carcinoma - Huang, Hui; Liu, Jie; Wang, Xiaolei; Liu, Shaoyan (Frontiers in Endocrinology, 2022)
Objective To observe the outcomes of nonsuspicious contralateral nodules with active surveillance in patients with papillary thyroid carcinoma (PTC). Methods Consecutive patients who underwent lobectomy for PTC were retrospectively reviewed. Patients with one or more nodules with nonsuspicious ultrasonography (US) features in the contralateral lobe were included. Abstract Objective To observe the outcomes of nonsuspicious contralateral nodules with active surveillance in patients with papillary thyroid carcinoma (PTC). Methods Consecutive patients who underwent lobectomy for PTC were retrospectively reviewed. Patients with one or more nodules with nonsuspicious ultrasonography (US) features in the contralateral lobe were included. Results Two hundred and eighty-three patients were included. All patients underwent thyroid lobectomy with ipsilateral central neck dissection. A total of 123 patients (43.5%) were classified as ATA low-risk, and 160 patients (56.5%) were classified as intermediate-risk. The median size of the contralateral nodules was 3 mm (range, 2 to 16 mm). After a period of follow-up, the median size change of contralateral nodules was 0 mm (range, -7 to 8 mm). Eight patients (2.8%) had nodule growth >3 mm, 223 patients (78.8%) had stable or decreased nodules, and 52 patients (18.4%) had no detectable nodules. Nodules in 24 patients had suspicious US features, 16 of which were diagnosed with PTMC by either cytology after FNA (in 7 patients) or histopathology after completion thyroidectomy (in 9 patients). Another four patients received completion thyroidectomy for ipsilateral cervical lymph node metastasis. The 5-year residual lobe recurrence (RLR) rate and recurrence-free survival (RFS) rate were 7.4% and 89.8%, respectively. Multivariate analysis showed that multifocality and ATA intermediate-risk were independent predictors for RLR (HR4.083, 95%CI 1.480-11.261, P = 0.007; HR 6.045, 95%CI 1.370-26.662, P = 0.017, respectively) and RFS (HR 5.240, 95%CI 2.114-12.991, P < 0.001; HR 5.223, 95%CI 1.353-17.765, P = 0.008, respectively). Conclusions Active surveillance for nonsuspicious contralateral nodules in patients with low-intermediate risk PTC is safe. Multifocality and ATA intermediate-risk are predicters for recurrence. Early detection and salvage surgery are effective.